Psychophysiological stress-reactivity in clinical and non-clinical voice-hearers - Baumeister, David; Pillinger, Toby; Howes, Oliver; Peters, Emmanuelle (Schizophrenia research, 2021)
Background: Psychosis is associated with dysregulation of psychophysiological stress-reactivity, including in subjective, autonomic nervous system (ANS) and hypothalamic-pituitary-adrenal (HPA) parameters. Aims: This study investigated whether dysregulated psychophysiological stress-reactivity is specifically associated with auditory verbal hallucinations (AVHs) or psychosis more generally by comparing voice-hearers with and without a need for care. Method: Clinical (n = 20) and non-clinical voice-hearers (n = 23), as well as a healthy control group with no voices (n = 23), were compared on HPA and ANS responses, and subjective reactivity, to a psychophysiological stress paradigm, the socially evaluative cold pressor test. Results: Measures of HPA function in both clinical and non-clinical voice-hearers diverged from non-voicehearing controls. Clinical participants showed a blunted peak response compared to both non-clinical groups (p = 0.02), whilst non-clinical voice-hearers showed, at trend-level, reduced cortisol levels during stress exposure compared to both clinical voice-hearers (p = 0.07) and healthy controls (p = 0.07), who unexpectedly did not differ from each other (p = 0.97). Clinical participants showed greater subjective stress levels than both nonclinical groups (p < 0.001), as well as greater anticipatory stress (p = 0.001) and less recovery. There were no differences between groups on parameters of the ANS (all p > 0.05). Conclusions: Dysregulated psychophysiological stress-function is present in clinical voice-hearers, and partially discriminates them from non-clinical voice-hearers. Overall, the present findings identified specific potential psychophysiological markers of risk and resilience in auditory verbal hallucinations and need for care.
Gesehen am 20.10.2021